2016
DOI: 10.21098/bemp.v19i1.601
|View full text |Cite
|
Sign up to set email alerts
|

The Islamic Banking and the Economic Integration in Asean

Abstract: The efficiency level of the banking industry is the most important indicator to identify the soundness of banking system. This paper use non parametric frontier approach, DEA, to analyze the Islamic bank efficiency in ASEAN. We use price of deposit from customers, deposits and placements of banks, labor, and others operational expenditures as control variabel, and using financing, deposits and placements on other insitution, securities, others investment as output variabel. We found that the mix bank is the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
1
11
0
2
Order By: Relevance
“…The study conducted by Solihin et al (2016) using DEA found that in the ASEAN area, competition between Islamic banks only appears in Indonesia and Malaysia and that Brunei, the Philippines, and Singapore have only one Islamic bank each. It was identified that Islamic banks in Indonesia would show lower efficiency than those in Malaysia unless they could reduce their costs of labour and other operational expenses.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Solihin et al (2016) using DEA found that in the ASEAN area, competition between Islamic banks only appears in Indonesia and Malaysia and that Brunei, the Philippines, and Singapore have only one Islamic bank each. It was identified that Islamic banks in Indonesia would show lower efficiency than those in Malaysia unless they could reduce their costs of labour and other operational expenses.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The implementation of Islamic banking in many Muslim majority countries would strengthen banking market competition. The quality of management of Islamic banking would become a crucial factor which could affect the efficiency of operation of the Islamic banking sector, highlighting the importance of efficiency level measurement for all existing Islamic banks in ASEAN countries (Solihin, Achsani, & Saptono, 2016).…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…Perkembangan Kenerja Perbankan 2015(Statistik Perbankan Indonesia, 2015 Berbagai kondisi yang terjadi tersebut menjadi tantangan bagikbank syariah yang ada di Indonesia. Untuk dapat tetap bertahan dan bersaing maka diperlukan sebuah evaluasi terhadap kinerja, salah satunya dengan melihat efisiensi sehingga dapat menyusun strategi yang diperlukan untuk menghadapai segala tantangan yang ada (Solihin et al, 2016). Efisiensi merupakan suatu hal yang penting bagi dunia perbankan dalam melihatkkemampuan bank dalam menggunakan input yang ada untuk menghasil output yang maksimal agar dapat mampu bertahanhdan menghadapi persaingankdalam industri perbankan (Setyowati, 2019).…”
Section: Pendahuluanunclassified
“…Current government policies that pay more attention to the development of maritime axis is also a driver for law enforcement in Indonesian sea. There are 3 (three) Fisheries Management Areas (FMA) that are often victims of illegal fishing practices: FMA of South China Sea, there is decrease in stock density and demersal fish species size; Arafura Sea FMA there is a decrease in stock and weight of shrimp; and FMA of the Indian Ocean, a decrease in the number of catch and weight of tuna [21]. IUU Fishing is a factor that causes Indonesia can not maximally utilize its marine wealth.…”
Section: Causative Factors and Value Losses Due To Iuu Fishingmentioning
confidence: 99%
“…Supervision and Control of Marine and Fishery Resources (Pengawasan dan Pengendalian Sumber Daya Kelautan dan Perikanan/P2SDKP) discloses, some of the economic losses due to IUU fishing are (1) fishery levies paid by the tariff of Indonesian ship; (2) fuel subsidies enjoyed by unauthorized foreign ships; and (3) stolen fish production (volume and value). This loss is the impact of illegal fishing because of the direct loss of catch value that should be accepted by every coastal state [22,21,23,24].…”
Section: Causative Factors and Value Losses Due To Iuu Fishingmentioning
confidence: 99%